Recombinant FSH increases live birth rates as compared to clomiphene citrate in intrauterine insemination cycles in couples with subfertility: a prospective randomized study. (June 2015) - Erdem, Mehmet; Abay, Seraf; Erdem, Ahmet; Firat Mutlu, Mehmet; Nas, Esra; Mutlu, Ilknur; Oktem, Mesut
Abstract: Objective: To compare the efficacy of intrauterine insemination (IUI) cycles undergoing ovarian hyperstimulation with recombinant FSH (rFSH) or clomiphene citrate (CC) in couples with unexplained and male subfertility. Study design: Two hundred and nineteen subfertile couples were enrolled in this randomized prospective study. Patients were randomly assigned to receive 75 IU rFSH or 100 mg CC for two cycles. Cycles with more than four dominant follicles and/or serum E2 levels higher than 1500 pg/ml were cancelled. Primary outcomes were live birth rates per patient and per cycle, secondary outcomes were clinical and multiple pregnancy rates. Results: One hundred and nine women received rFSH and 110 received CC. Both cumulative clinical pregnancy and live birth rates per patient were significantly higher in gonadotropin group (43.1% and 37.6%) as compared to CC group (28.2% and 20%) ( p < 0.05 and p < 0.01, respectively). Live birth rate per cycle were significantly higher in gonadotropin group (24.3%) in comparison with CC group (13.8%) ( p < 0.05). However, clinical pregnancy rate per cycle was not different between groups (28.4% vs 20%) ( p > 0.05). There was no significant difference between gonadotropin and CC group groups in terms of multiple pregnancy rates (10.4% vs 12.5%, p > 0.05). Continuous variables were compared with Student's t test. Categorical variables were compared with Chi square test. Conclusion: rFSH has significantly higher cumulative clinical pregnancy and live birth rates when compared to CC with similar multiple pregnancy rates in subfertile patients undergoing IUI.